1996
DOI: 10.2136/sssaj1996.03615995006000040036x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Relations between Oat Residue and Ceramic Spheres when Incorporated Sequentially by Tillage

Abstract: Spatial characterization of crop residues and agrichemicals incorporated by tillage is needed to interpret biomass‐related soil processes. This study presents such a characterization. We first described oat residue (Avena sativa L.) and green‐sphere distributions produced by chisel plow (CP) and moldboard plow (MP) tillage and then described red‐sphere distributions when incorporated during secondary tillage. Finally the co‐location of incorporated oat residue and colored spheres was characterized. Green and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 0 publications
3
35
0
Order By: Relevance
“…NT treatment resulted in the absence of soil disturbance, with the straw remaining on the soil surface. In contrast, under RT and PT treatments, an excess of 90 and 60 % of incorporated straw might be buried at depths of 0-11 cm and 10-20 cm, respectively (Allmaras et al 1996). Li et al (2001) reported straw decomposition rates were closely related to SI depths, in decreasing order from 5 to 15 cm to the surface soil.…”
Section: Si Effects On Soil Cmentioning
confidence: 98%
“…NT treatment resulted in the absence of soil disturbance, with the straw remaining on the soil surface. In contrast, under RT and PT treatments, an excess of 90 and 60 % of incorporated straw might be buried at depths of 0-11 cm and 10-20 cm, respectively (Allmaras et al 1996). Li et al (2001) reported straw decomposition rates were closely related to SI depths, in decreasing order from 5 to 15 cm to the surface soil.…”
Section: Si Effects On Soil Cmentioning
confidence: 98%
“…Allmaras et al (1996) characterized the depth distributions of oat residues and ceramic spheres incorporated by tillage into the top 30 cm. Green spheres served as a residue tracer under primary tillage, followed by secondary tillage of red spheres as a tracer or surrogate for herbicides.…”
Section: Infiltration Rates and Capacitymentioning
confidence: 99%
“…the presence or absence of mulch on the soil surface or the spreading of fragments in the soil, modifies the physical, biological and chemical properties of soil, such as water content, temperature, O 2 content (Allmaras et al 1996), N content, pH and the composition of the decomposer community (Holland and Coleman 1987). The reduced rate of decomposition usually observed under field conditions on the surface (Seneviratne et al 1998) may be attributed to a limited contact between soil and plant residues.…”
Section: Introductionmentioning
confidence: 99%